Redemption or Condemnation? A Long-Term Follow-up of the Desistance Patterns of Sex Offenders - Kras, Kimberly Raye (2014)
Desistance is one of most important topics in criminology. Why some offenders stop offending and why others continue has been long been a question with far-reaching theoretical and empirical implications. Despite the extensive literature on desistance, most of the research examines offenders as a single group, an approach which might overlook differences between individuals by offense type. One offender group that has not been investigated in depth is sex offenders. Sex offenders are an important group to study because they present concerns to public safety and are the subject of much legislation and criminal justice policy. A substantial amount of research has been devoted to understanding why sex offenders commit the crimes they do and recidivism. However, fewer studies have examined about how and why they might desist from offending. There are reasons to expect that the desistance process may operate differently for sex offenders as compared to other types of offenders. The public considers sex offenders to be among the most dangerous offenders, who reoffend at very high rates, which has resulted in legislation that increases surveillance and restrictions intended to prevent future offending. Despite a widespread belief that sex offenders are not amenable to rehabilitation, most states require sex offenders to participate in treatment that addresses sexual deviance using cognitive behavioral therapy (CBT). The differences between sex offenders and other types of offenders suggests that the path to desistance for sex offenders might also occur differently than for other types of offenders who are not subject to the same public scrutiny, legal restrictions, and therapeutic interventions. To examine the nature of the desistance process for sex offenders, this dissertation uses a longitudinal qualitative analysis of current and former sex offenders at two points in time: release from prison (Phase 1) and a three-year follow-up (Phase 2). Findings show that patterns of desistance are more complex than the desister-persister dichotomy suggests. This study explores the relationship of cognitive scripts to these categories, discusses the influence of treatment on desistance, and presents additional cognitive scripts specific to the reentry experience of sex offenders. Implications of this research are also discussed